Design and simulation of high-speed nanophotonic electro-optic modulators - Kaunga-Nyirenda, S.N.; Dias, H.K.; Lim, J.J.; Bull, S.; Malaguti, S.; Bellanca, G.; Larkins, E.C. (2014)
In this work, an ultracompact electro-optic modulator based on refractive index modulation by plasma dispersion effect in PhC all-optical gate (AOG) is proposed. The index modulation is achieved by applying a time-varying bias voltage across the electrical contacts of the AOG. The proposed modulator has potential for high-speed operation, with bandwidths in excess of 30GHz achievable.